Modulation of inflammation by interleukin‐27. Issue 6 (31st July 2013) - Bosmann, Markus; Ward, Peter A.
Abstract : Review on how IL‐27 balances inflammation during infectious and autoimmune diseases. Abstract : A growing body of evidence suggests an essential role of the heterodimeric cytokine, IL‐27, for regulating immunity. IL‐27 is composed of two subunits (p28 and EBI3) and is classified as a member of the IL‐12 family of cytokines. APCs have been recognized as a major cellular source of IL‐27 following activation with microbial products or IFNs (types I and II). In this review, we describe the current knowledge of the implications of IL‐27 during the pathogenesis of infectious and autoimmune diseases. Experimental studies have used genetically targeted IL‐27RA−/− mice, EBI3−/− mice, and p28−/− mice or involved study designs with administration of bioengineered IL‐27/IL‐27RA homologs. Whereas many reports have described that IL‐27 suppresses inflammation, we also review the current literature, suggesting promotion of inflammation by IL‐27 in some settings. Recent advances have also been made in understanding the cross‐talk of cleavage products of the complement system with IL‐27‐mediated immune responses. Additional data on IL‐27 have been obtained recently by observational studies in human patients with acute and chronic inflammatory diseases. Collectively, the findings from the past decade identify IL‐27 as a critical immunoregulatory cytokine, especially for T cells, whereas some controversy is fueled by results challenging the view of IL‐27 as a classical silencer of inflammation.